2021
DOI: 10.1002/aic.17390
|View full text |Cite
|
Sign up to set email alerts
|

Capture of dilute methane with a novel dynamic‐feed dual‐reflux pressure swing adsorption process

Abstract: Dual‐reflux pressure swing adsorption (DR‐PSA) is a state‐of‐art adsorption technology claiming to achieve both high product purity and recovery. However, its performance is inevitably limited by the gas mixing problem at the feed inlet position in adsorption columns, where a discontinuity in the columns' axial concentration profiles disturbs the separation. Here, we developed a dynamic‐feed DR‐PSA (DF‐DR‐PSA) process to solve the mixing problem and obtain better separation performance by introducing multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The concentration of components in the feed gas stream is generally different from that in the reflux flow, resulting in the so-called "mixing problem," which manifests as the discontinuity of axial concentration curves at the injection position. The mixing problem has been reported and investigated in the open literature 23,42,44,48 and has been confirmed…”
Section: Effect Of Feed Inlet Positionmentioning
confidence: 64%
See 3 more Smart Citations
“…The concentration of components in the feed gas stream is generally different from that in the reflux flow, resulting in the so-called "mixing problem," which manifests as the discontinuity of axial concentration curves at the injection position. The mixing problem has been reported and investigated in the open literature 23,42,44,48 and has been confirmed…”
Section: Effect Of Feed Inlet Positionmentioning
confidence: 64%
“…The concentration of components in the feed gas stream is generally different from that in the upstream reflux flow, resulting in the so‐called “mixing problem,” which manifests as the discontinuity of axial concentration curves at the injection position. The mixing problem has been reported and investigated in the open literature 23,42,44,48 and has been confirmed to have negative impacts on the separation performance of the process. The effect of feed position ( Z F ) was investigated by changing the Z F between 0.4 and 0.9.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A range of novel PSA processes has been proposed and demonstrated, particularly for the purpose of upgrading dilute mixtures of CH 4 in N 2 or air. May et al investigated the separation of CH 4 and N 2 using dual-reflux PSA with activated carbon, Engelhard titanosilicate type 4 (ETS-4), and ionic liquidic zeolites as adsorbents via experiments and simulations. Results showed that optimized DR-PSA processes using Norit RB3 adsorbents can upgrade dilute methane (2.4%) to 35.7%, leaving a clean nitrogen vent bearing 3000 ppmv methane, which is promising in the reduction of fugitive methane emissions. Guo et al employed a triple-reflux strategy to separate CH 4 /N 2 /He by opening a third channel on DR-PSA and achieved three high-purity streams simultaneously.…”
Section: Introductionmentioning
confidence: 99%